The Mediating Role of Work-Life Balance in the Relationship Between Workload and Employee Performance (A Study at Statistics Indonesia (BPS) Across Banten Province) - Riza F. Ramadhan; Wawan Prahiawan; Ali Imron; Asro Harun (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study examines the effect of workload on employee performance and investigates the mediating role of work-life balance among employees of Statistics Indonesia (BPS) across Banten Province. The study is motivated by performance gaps, increasing work demands, and the imbalance between workforce availability and workload requirements. A quantitative approach with a cross-sectional survey design was employed, involving employees from BPS offices throughout Banten Province. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that workload has a negative but insignificant effect on employee performance. However, workload significantly and negatively affects work-life balance, while work-life balance has a significant positive effect on employee performance. Furthermore, work-life balance fully mediates the relationship between workload and employee performance. These findings indicate that the impact of workload on employee performance occurs primarily through employees’ ability to maintain a healthy balance between work and personal life. Therefore, organizations should prioritize workload management and work-life balance initiatives to sustain and improve employee performance.